Measurement of renal anatomy for prediction of lower-pole caliceal stone clearance: reproducibility of different parameters - Knoll, Thomas; Musial, Anton; Trojan, Lutz; Ptashnyk, Taras; Michel, Maurice Stephan; Alken, Peter; Köhrmann, Kai-Uwe (Journal of endourology, 2003)
Background and Purpose: The architecture of the lower renal pole seems to have a considerable influence on caliceal stone clearance after different therapeutic modalities. The published data are partially inconsistent, and publications on reproducibility are completely lacking. The aim of this study was to evaluate the intraobserver and interobserver reproducibility of different measures of lower-calix anatomy. - - Materials and Methods: We studied the intraobserver and interobserver reproducibility of parameters describing the lower-pole anatomy that are significant for treatment outcome. Forty renal units without urologic disease were analyzed by five independent urologists. Infundibular length (IL), infundibular width (IW), and lower infundibulopelvic angles (LIP) were measured by the Elbahnasy (LIP I), Keeley (LIP II), and Gupta (LIP III and LIP IV) methods. Statistical analysis of each parameter and investigator was performed. - - Results: All LIP angles showed low interobserver correspondence: correlation coefficients (CC) did not exceed 0.44 (P < 0.05). Even the relatively clearly defined parameters IW and IL achieved CCs of only 0.63 and 0.49, respectively. The intraobserver correlation achieved better results: 0.73 (LIP I), 0.84 (LIP II), 0.73 (LIP III), 0.65 (LIP IV), 0.88 (IL), and 0.82 (IW). With the Elbahnasy method, almost all renal units were classified as favorable for stone persistence after shockwave lithotripsy. With the Keeley and Gupta methods, more than 50% of the kidneys were defined as having low clearance probability. - - Conclusions: Assessment of the chosen parameters is difficult and shows high interobserver variation. Inexperience in measuring the specific angles and low imaging quality can limit correct evaluation. The large number of kidneys with anatomy inappropriate for clearance of lower-pole stones may explain the poor outcome of shockwave treatment for stones in a lower calix. Prospective studies will determine the clinical value of anatomic assessments.
Gesehen am 11.03.2022
Published Online: 6 Jul 2004